2014
DOI: 10.1073/pnas.1318690111
|View full text |Cite
|
Sign up to set email alerts
|

Quorum sensing controls hyphal initiation in Candida albicans through Ubr1-mediated protein degradation

Abstract: Candida albicans is the most common cause of invasive fungal infections in humans. Its ability to undergo the morphological transition from yeast to hyphal growth forms is critical for its pathogenesis. Hyphal initiation requires the activation of the cAMP-PKA pathway, which down-regulates the expression of NRG1, the major repressor of hyphal development. Hyphal initiation also requires inoculation of a small amount of C. albicans cells from overnight culture to fresh medium. This inoculation releases the inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
123
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(130 citation statements)
references
References 46 publications
6
123
1
Order By: Relevance
“…Farnesol is reported to exert its inhibitory effects on germ-tube formation through Ras1-Cyr1 (Davis-Hanna et al 2008). The release from farnesol inhibition when cells are inoculated from dense cultures into fresh media is essential for Nrg1 degradation, which requires the kinase Sok1 (Lu et al 2014). The SOK1 transcriptional repressor, Cup9, is rapidly degraded on release from farnesol inhibition through the E3 ubiquitin ligase, Ubr1, leading to the derepression of SOK1 transcription and Nrg1 degradation (Lu et al 2014).…”
Section: Quorum Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Farnesol is reported to exert its inhibitory effects on germ-tube formation through Ras1-Cyr1 (Davis-Hanna et al 2008). The release from farnesol inhibition when cells are inoculated from dense cultures into fresh media is essential for Nrg1 degradation, which requires the kinase Sok1 (Lu et al 2014). The SOK1 transcriptional repressor, Cup9, is rapidly degraded on release from farnesol inhibition through the E3 ubiquitin ligase, Ubr1, leading to the derepression of SOK1 transcription and Nrg1 degradation (Lu et al 2014).…”
Section: Quorum Sensingmentioning
confidence: 99%
“…The release from farnesol inhibition when cells are inoculated from dense cultures into fresh media is essential for Nrg1 degradation, which requires the kinase Sok1 (Lu et al 2014). The SOK1 transcriptional repressor, Cup9, is rapidly degraded on release from farnesol inhibition through the E3 ubiquitin ligase, Ubr1, leading to the derepression of SOK1 transcription and Nrg1 degradation (Lu et al 2014). Therefore, the temporary clearing of Nrg1 protein during hyphal initiation is achieved by two independent regulations: the cAMP-PKA-dependent transcriptional downregulation of NRG1 and degradation of Nrg1 protein triggered by the release from farnesol inhibition.…”
Section: Quorum Sensingmentioning
confidence: 99%
“…The SspB-Als3 interaction is involved in biofilm development in which bacteria and fungi cooperate at the cellular and molecular level to generate a robust mixed microbial community (Whitmore & Lamont, 2011). Community composition may be regulated by extracellular signalling molecules such as autoinducer-2 (AI-2) (McNab et al, 2003;Bamford et al, 2009), farnesol (Bamford et al, 2009;Lu et al, 2014), Nacetyl-D-glucosamine (Naseem et al, 2011) and homoserine lactones (Hogan et al, 2004). In addition, the quorum-sensing (QS) molecule, competence stimulating peptide (CSP), produced by Streptococcus mutans inhibits hypha formation by C. albicans (Jarosz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that Nrg1 levels are downregulated during hyphal initiation by two distinct mechanisms in C. albicans: transcriptional repression by cAMP-PKA signaling and Ubr1/Cup9/Sok1-mediated protein degradation that is triggered by release from farnesol inhibition (17,41). Nrg1 begins to disappear within minutes upon serum induction at 37°C in wild-type cells only when transcriptional repression and protein degradation occur simultaneously (41). We found that Nrg1 levels are not downregulated in the cbk1⌬/⌬ mutant and Als3 is not expressed in the absence of Cbk1 (Fig.…”
Section: Discussionmentioning
confidence: 99%